Chronic retinoic acid treatment suppresses adult hippocampal neurogenesis, in close correlation with depressive‐like behavior. Issue 7 (7th March 2016) - Hu, Pu; Wang, Yu; Liu, Ji; Meng, Fan‐Tao; Qi, Xin‐Rui; Chen, Lin; van Dam, Anne‐Marie; Joëls, Marian; Lucassen, Paul J.; Zhou, Jiang‐Ning
ABSTRACT: Clinical studies have highlighted an association between retinoid treatment and depressive symptoms. As we had shown before that chronic application of all‐trans retinoic acid (RA) potently activated the hypothalamus‐pituitary‐adrenal (HPA) stress axis, we here questioned whether RA also induced changes in adult hippocampal neurogenesis, a form of structural plasticity sensitive to stress and implicated in aspects of depression and hippocampal function. RA was applied intracerebroventricularly (i.c.v.) to adult rats for 19 days after which animals were subjected to tests for depressive‐like behavior (sucrose preference) and spatial learning and memory (water maze) performance. On day 27, adult hippocampal neurogenesis and astrogliosis was quantified using BrdU (newborn cell survival), PCNA (proliferation), doublecortin (DCX; neuronal differentiation), and GFAP (astrocytes) as markers. RA was found to increase retinoic acid receptor‐α (RAR‐α) protein expression in the hippocampus, suggesting an activation of RA‐induced signaling mechanisms. RA further potently suppressed cell proliferation, newborn cell survival as well as neurogenesis, but not astrogliosis. These structural plasticity changes were significantly correlated with scores for anhedonia, a core symptom of depression, but not with water maze performance. Our results suggest that RA‐induced impairments in hippocampal neurogenesis correlate with depression‐like symptoms but not with spatial learning and memory in this design. Thus, manipulations aimed to enhance neurogenesis may help ameliorate emotional aspects of RA‐associated mood disorders. © 2016 Wiley Periodicals, Inc.